Sebaran Kelayakan Air Sumur Sebagai Air Baku Minum di Kelurahan Sekaran Kecamatan Gunungpati Kota Semarang Tahun 2018 - Oki, Rahayu Eklesia; Ananto, Aji; Tukidi, Tukidi (Geo-Image, 2019)
Sekaran village has a dense population due to the existence of Semarang State University. This has an effect on environmental conditions, especially the availability of water for daily activities that have an impact on increasing waste water. This situation affects groundwater quality. The purpose of this study was to determine the feasibility of well water as drinking raw water based on mandatory parameters and analyze the effect of well construction with well water pollution. This study uses several methods of data collection, namely observation methods, questionnaires, documentation, and laboratory tests. The results of this study indicate that well water in Sekaran Village is only 7 (28%) samples that are feasible to be used as drinking raw water, 18 (72%) other samples are not feasible. Construction of well buildings shows the influence of pollutant sources, on the construction of wells that do not meet the requirements proved to be unfit for use as drinking raw water.